Implementing the Use of Flashcards to Improve Students’ Vocabulary Mastery; Classroom Action Research - Azahra, Ngemas Humairo Nur; Isnaini, Septiana; Sudarmaji, Imam; Nuraini, Hery; Forsia, Lastry; Nirmala, Nirna (Universitas Pahlawan Tuanku Tambusai, 2024)
One of the problems that causes students to have difficulty in improving their English skills is the lack of vocabulary mastery. This research aims to determine whether the use of flash card teaching media can improve students' vocabulary mastery. This research uses a classroom action research design with a quantitative method conducted on students in the fourth grade at SDN Pondok Jagung Timur in Tangerang Selatan. The researcher presented the result and the analysis of data collected that consisted of pre-test, cycle 1, and post-test. Each cycle of the research consists of planning, action, observation, and reflection activities. In the research, there are some steps before cycle 1, there are observation and pre-test. The last step after cycle 1 is the post-test. The result of the research showed that Flash cards could improve the students’ mastery of vocabulary. It can be identified from the mean score of the test which increased from 69,8 in the pre-test to 91,0 in the post-test. The use of flashcards may attract the student’s attention to the lesson well. It also might improve the participation of students in learning. They were not shy anymore and were motivated to attend the instructional process